Educators of Healthcare Professionals Agreeing a Shared Purpose - Browne, Julie (Cardiff University Press, 2021)
Healthcare education is a discipline in its own right, and while each profession has its own distinctive body of clinical knowledge, in educational terms there is much that all professions share. Yet recognition for the healthcare educator role is often lacking. A more collaborative approach to the professional development of healthcare educators is needed in response to this and also to the rise of interprofessional and multiprofessional teamworking. Not all healthcare professions have guidelines for training their educators, and those that do have slightly different standards, which can lead to misunderstanding and miscommunication. It is in the interest of all healthcare professions that their professional bodies work more closely together to consider how healthcare educators can be supported as a distinct body with unique expertise and skills. This monograph reports on an 18-month long research project - the Healthcare Educators' Values and Activities Study (HEVAS) - which aimed to establish the views of health professions educators, regulators, learned societies and professional bodies on the shared values and key activities undertaken by all healthcare professions educators. The project was funded by Health Education England and the Wales Deanery at Health Education and Improvement Wales. Nine central values and 24 activities were identified after a five-stage research process involving hundreds of participants drawn from over 20 healthcare professions. A variety of methods was used to establish a broad and clear consensus, demonstrating conclusively that healthcare professions educators share a strong set of values around the importance of professional healthcare education to safeguarding excellence in clinical practice and patient care, both now and for the future. While each profession develops its students, trainees and practitioners in its own way, the fundamental work of the healthcare educator is broadly similar, regardless of clinical specialty or profession. This new insight provides solid academic underpinning for multi-professional and interprofessional practice in healthcare education, and offers a new shared perspective on the future for healthcare education and healthcare educators.